Application of desirability-function and RSM to optimise the multi-objectives while turning Inconel 718 using coated carbide tools. (1st January 2013) - Manohar, M.; Joseph, Jomy; Selvaraj, T.; Sivakumar, D.
Researchers always focus their attention to bring out process improvements resulting in improved product quality and increased production simultaneously. Such efforts gain significance in the case of Inconel 718, where the cost saving in producing components is higly rewarding. Turning experiments were conducted using Taguchi's methods and experimental data was collected. Response surface models were generated for each response depicting the role of the input variables and the effect of their interaction. Almost all the research work in response surface methodology (RSM) has been aiming at the problems where only one response of interest is addressed. With the aim of optimising the multi-objectives, desirability function approach (DFA) was adopted. Surface and contour plots were generated for the RSMs evolved using MATLAB. This work resulted in identifying the optimised set of turning parameters for Inconel 718 using coated carbide tools satisfying the multi-objectives.